Effective instructional design for value dominant education in Malaysian public universities / Fattawi Mokhtar and Mohd Nor Mamat - Mokhtar, Fattawi; Mamat, Mohd Nor (Research Management Institute (RMI), 2008)
Education is an important medium to ensure sustainability of human civilization. Holistic education must contain three main objectives to be achieved; cognitive, psychomotor and affective domains which involve knowledge transfer, skill enhancement and value or attitude inculcation. Our national education today regardless in primary, secondary or tertiary level seems to be more on producing graduates with knowledge and skill, but not much on value as major. This doesn't mean that value-education should be dominant in educational curriculum but it could be dominant within specific value dominant courses. Ethics or moral courses are among value-dominant courses that must prioritize value or attitude effects as main objectives. This needs different and specific instructional design (ID) in which value become major objectives in learning outcomes, activities, evaluation and etc. The study selected environmental ethics course as a case study. The study has recognized unique instructional activities for three different groups in UiTM A, UiTM B and UPSI (n=108). ID also includes learning objectives, learning object and content itself, other than instructional activities. All these have been identified using document review and interviews. The effects of environmental attitude (EA) have been measured using New Environmental Paradigm (NEP) which is endorsed by UNESCO and Behaviour-based Environmental Attitude Test by F J. Kaiser (2007) at the end of the semester to identify the effects of environmental paradigm and attitude. In this study, the result ofEA would be correlated with the different unique objectives, contents and activities to recognize the best ID for producing value effects, which is the environmental attitude. This led to few main findings as the best practices; religious elements, practical contents and environmental-related activities which have affected much on student's paradigm and attitude towards environment.